Estudio SocioJurídico de los Abogados en Libre Ejercicio ProfesionalEl Caso Ecuatoriano - Dávila Smith, Karla María (2018)
Resumen:The present end-of-degree research is important to me as a student because it contributes with RELEVANT INFORMATION regarding the lawyers in free professional practice in Ecuador. This thesis will allow us to analyze the work of the lawyer and the State Institutions that must do with their work, as well as the legal regulations so that the lawyer can carry out his work. This work will allow to know the technical and intellectual efficiency that the lawyers of Ecuador contribute to their clients to defend in judicial cases within the national territory. The statistics made in the result generate a technical knowledge so that the student in Law can feel the reality of the lawyer in free exercise in Ecuador.